دور المراجعة الداخلية في تحسين جودة المعلومات المحاسبية – دراسة ميدانية - أميرة, حابي; دنيا, خنوفة; كريمة, نوبلي (جامعة الوادي - University of Eloued, 2023)
"تهدف هذه الدراسة إلى توضيح دور المراجعة الداخلية في تحسين جودة المعلومة المحاسبية حيث يعتبر وجود المراجعة الداخلية الفعالة والقوية بالمؤسسة من شأنه أن يعزز من تحقيق الجودة على مستوى المعلومة المحاسبية. ولتحقق هدف الدراسة تم تصميم استبيان وجه لعينة من محاسبين مراجعين داخلين محافظي الحسابات وأخرى، والقيام بتحليل آراء وإجابات المستجوبين باستخدام اختبارات ومعالجات إحصائية مناسبة بهدف الوصول إلى نتائج ذات دلالة تدعم موضوع البحث، وتوصلنا في دراستنا إلى مجموعة من النتائج أهمها: أن المراجع الداخلي دور كبير في تأكيد الثقة بالمعلومة المحاسبية خاصة ما توفرت فيه المؤهلات التي تدعمه في ذلك، والالتزام بتطبيق المعايير والأسس والمبادئ التي تحكم المراجعة الداخلية، وبيان مدى أهمية استخدام تكنولوجية المعلومات في آلية المراجعة على ضبط فاعلية وكفاءة المراجعة وبالتالي جودة المعلومة المحاسبية من وجهة نظر مراجعي الحسابات ""This study aims to clarify the role of internal audit in improving the quality of accounting information, where the presence of effective and strong internal audit in the institution would enhance the achievement of quality at the level of accounting information. In order to achieve the aim of the study, a questionnaire was designed for a sample of internally audited accountants, accountants and others, and an analysis of the opinions and answers of the respondents was carried out using appropriate statistical tests and treatments in order to reach significant results that support the subject of the research. In our study, we reached a set of results, the most important of which are: In confirming confidence in accounting information, especially when the qualifications that support it are available, and commitment to applying the standards, foundations and principles that govern internal auditing, and indicating the importance of using information technology in the audit mechanism to control the effectiveness and efficiency of auditing and thus the quality of accounting information from the point of view of auditors "
Keywords: مراجعة داخلية، نظام المعلومات المحاسبي، جودة المعلومة المحاسبية. كفاءة المراجع الداخلي; internal audit, accounting information system, quality of accounting information. Efficiency of the internal auditor